Examining the differential effects of latent impulsivity factors on substance use outcomes in African American men. (June 2021) - Bertin, Lauren; Benca-Bachman, Chelsie E.; Kogan, Steven M.; Palmer, Rohan H.C.
Highlights: First study to assess structures of the UPPS-P in an exclusively African American sample. We examined the joint effects of latent factors derived from the UPPS-P on substance use outcomes. Deficits in Conscientiousness affected whether men had any future substance use problems. Abstract: African Americans have elevated substance use-related problems during adulthood despite initiating use later than individuals of other racial/ethnic backgrounds. The present study first validated the structure of the UPPS-P Impulsive Behavior Scale and then examined impulsivity as a prospective risk factor for future alcohol, cannabis, and tobacco use, as well as generalized substance problems, in African American men. Data were drawn from the African-American Men's Project, which recruited participants ( N WAVE-1  = 504; Mean ageWAVE-1  = 20.7; N WAVE-3  = 379; Mean ageWAVE-3  = 23.6) from rural counties of Georgia. Participants responded to an adapted version of the UPPS-P at Wave 1. Confirmatory factor analyses determined that a 5-factor model of impulsivity and a 3-factor hierarchical model of impulsivity described the data equally well, in comparison to 1-factor, 4-factor, or bifactor models. This supports that the structure of the abbreviated UPPS-P in African Americans is likely consistent with observations in White, Hispanic/Latino, and admixed samples. Notably, all second-order factors of the UPPS-P are not alike in predicting substance use outcomes when examined jointly in African American men. Only Deficits in Conscientiousness, which is a second-order factor comprised of Lack of Premeditation and Lack of Perseverance, affected whether individuals met any criteria for future substance use problems. Our findings provide novel insight into the relationship between impulsivity and substance involvement during emerging adulthood in African American men.